Development of an efficient magnetically separable nanocatalyst: theoretical approach on the role of the ligand backbone on epoxidation capability. Issue 112 (29th October 2015) - Adhikary, Jaydeep; Datta, Arnab; Dasgupta, Sanchari; Chakraborty, Aratrika; Menéndez, M. Isabel; Chattopadhyay, Tanmay
Abstract : The epoxidation property of an asymmetric iron complex has been experimentally and theoretically verified. This catalyst further conjugated with dopamine modified Fe3 O4 to obtain magnetically separable nano-catalyst. Abstract : Three chiral Schiff base ligands H2 L 1, H2 L 2, H2 L 3 have been synthesized by treating ( R )-1, 2-diaminopropane separately with 3, 5-dichlorosalicylaldehyde, 3, 5-dibromosalicylaldehyde and 3, 5-diiodosalicylaldehyde, respectively. Three new asymmetric Fe III complexes, namely, FeL 1 Cl (1 ), FeL 2 Cl (2 ), FeL 3 Cl (3 ) have been prepared from their corresponding ligands. The crystal structure of2 reveals that the complexes are mononuclear in nature. Circular dichroism (CD) studies suggest that the ligands and their corresponding complexes contain an asymmetric center. The catalytic activity of these complexes toward the epoxidation of alkenes has been investigated in the presence of iodosylbenzene (PhIO), in two solvents CH3 CN and CH2 Cl2 . The epoxide yield suggests that the order of their catalytic efficiency is3 >2 >1 . This trend as well as the role of substitution on the ligand backbone on alkene epoxidation has also been confirmed by density functional theory (DFT) calculations. For further adaptation, we attached our most efficient homogeneous catalyst, 3, with surface modified magnetic nanoparticles (Fe3 O4 @dopa) and thereby obtained the new magnetically separable nanocatalyst Fe3 O4 @dopa@FeL 3 Cl. This catalyst has been characterized and its olefin epoxidation ability investigated in similar conditions to those used for homogeneous catalysts. The enantiomeric excess of the epoxide yield reveals the retention of chirality of the active site of Fe3 O4 @dopa@FeL 3 Cl. The catalyst can be easily recovered by magnetic separation and recycled several times without significant loss of its catalytic activity.